Bullying and Harassment as a Consequence of Workplace Change in the Australian Civil Service: Investigating the Mediating Role of Satisfaction With Change Management. (March 2023) - Kleizen, Bjorn; Wynen, Jan; Boon, Jan; de Roover, Jolijn
Public sector organizations frequently restructure due to shifting management trends, crises, and political developments. Earlier research indicates that the sometimes-drastic reforms implemented in government strongly affect employees, causing psychosocial effects such as frustration, stress, and negative work environments. This may in turn increase the likelihood of severe phenomena such as workplace bullying and harassment. It remains unclear, however, how public organizations can introduce changes while preventing side-effects such as bullying and harassment. The goal of this article is twofold. First, we test whether evidence on the relationship between workplace change and bullying and harassment holds when using a large, public sector-wide sample. Second, we investigate whether satisfaction with change management plays a mediating role. Using cross-sectional and strata-based panel data analyses on Australian data, results indicate a positive relationship between workplace change and workplace bullying and harassment, but also suggest that satisfaction with change management mitigates this effect.